Using airborne thermal imaging data to measure near‐surface hydrology in upland ecosystems. Issue 6 (12th August 2014) - Luscombe, David J.; Anderson, Karen; Gatis, Naomi; Grand‐Clement, Emilie; Brazier, Richard E.
Abstract Upland ecosystems are recognized for their importance in providing valuable ecosystem services including water storage, water supply and flood attenuation alongside carbon storage and biodiversity. The UK contains 10–15% of the global resource of upland blanket peatlands, the hydrology and ecology of which are highly sensitive to external anthropogenic and climatic forcing. In particular, drainage of these landscapes for agricultural intensification and peat extraction has resulted in often unquantified damage to the peatland hydrology, and little is understood about the spatially distributed impacts of these practices on near‐surface wetness. This paper develops new techniques to extract spatial data describing the near‐surface wetness and hydrological behaviour of drained blanket peatlands using airborne thermal imaging data and airborne Light Detection and Ranging (LiDAR) data. The relative thermal emissivity (Ɛr) of the ground surface is mapped and used as a proxy for near‐surface wetness. The results show how moorland drainage and land surface structure have an impact on airborne measurements of thermal emissivity. Specifically, we show that information on land surface structure derived from LiDAR can help normalize signals in thermal emissivity data to improve description of hydrological condition across a test catchment in Exmoor, UK. An in situ field hydrological survey was used to validate these findings. We discuss how such data could be used to describe the spatially distributed nature of near‐surface water resources, to optimize catchment management schemes and to deliver improved understanding of the drivers of hydrological change in analogous ecosystems. Copyright © 2014 John Wiley & Sons, Ltd.